2009
DOI: 10.1111/j.1439-0531.2009.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Embryo Density onIn vitroDevelopmental Characteristics of Bovine Preimplantative Embryos with Respect to Micro and Macroenvironments

Abstract: To overcome developmental problems as a consequence of single embryo culture, the Well of the Well (WOW) culture system has been developed. In this study, we aimed to examine the effect of embryo densities with respect to both microenvironment and macroenvironment on developmental rates and embryo quality to get a deeper insight into developmentally important mechanisms. WOW diameter and depth significantly affected developmental rates (p < 0.05). WOWs with diameter of 500 μm reached significantly higher blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
(147 reference statements)
0
20
0
Order By: Relevance
“…It has been postulated to dilute metabolized toxic products while accumulating autocrine and/or paracrine factors released by the embryos, resulting in improved embryonic development [8,16,18,19]. Although the WOW system was developed initially for shortterm co-culture of zona-free mouse embryos to produce chimerae [34], the system has been shown to be useful in tracking individual zona-intact embryo cultured in groups [8,16,18,19], which presents an alternative to single embryo culture. Our future research will be aimed at developing a culture system for tracking individual embryo development following in vitro oocyte maturation (IVM) without imparirment of embryo development to the blastocyst stage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been postulated to dilute metabolized toxic products while accumulating autocrine and/or paracrine factors released by the embryos, resulting in improved embryonic development [8,16,18,19]. Although the WOW system was developed initially for shortterm co-culture of zona-free mouse embryos to produce chimerae [34], the system has been shown to be useful in tracking individual zona-intact embryo cultured in groups [8,16,18,19], which presents an alternative to single embryo culture. Our future research will be aimed at developing a culture system for tracking individual embryo development following in vitro oocyte maturation (IVM) without imparirment of embryo development to the blastocyst stage.…”
Section: Discussionmentioning
confidence: 98%
“…For this purpose, the well-of-the-well (WOW) system has been adapted in order to track the development of individual embryo [8,[16][17][18][19]. An embryo to culture dish volume ratio of 1:30 μl has been identified to be optimal when each embryo was cultured in a 0.27 μl micro-well, producing developmental rates up to the level of mass embryo production in cattle [18]. However, the optimal volume of medium droplets or density of embryos to be used with the WOW system remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, small culture volume as well embryo grouping have been proposed as two different strategies to improve embryo developmental potential [2,4,5,7,8,10,18,19,30] since autocrine and paracrine factors of embryonic origin are likely to mimick in vivo conditions [1,4,5,7,9,13]. In a recent review, Reed and coauthors [7] describe the impact of group versus individual cultures on embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning embryo physiology and metabolism have highlighted the importance of autocrine and paracrine growth factors affecting embryo development in vivo [1][2][3][4][5][6][7][8][9][10]. However, recent data have shown that preimplantation embryos promote their own development in vitro also in absence of paracrine factors secreted by the female reproductive tract [4,6,7,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation